The Origins of the Necessary and Proper Clause / [electronic resource] - Lawson, Gary; Miller, Geoffrey P.; Natelson, Robert G.; Seidman, Guy I. (Cambridge : Cambridge University Press, 2010)
The Necessary and Proper Clause is one of the most important parts of the US Constitution. Today this short thirty-nine-word paragraph is cited as the legal foundation for much of the modern federal government. Through three independent lines of research, the authors trace the lineage of the Necessary and Proper Clause to the everyday law of the Founding Era - the same law that American founders such as Madison, Hamilton, and Washington applied in their daily lives. Origins of the Necessary and Proper Clause are found in law-governing agencies, public administration, and corporations. Moreover, all of those areas were undergirded by common principles of fiduciary responsibility - reflecting the Founders' view that a public office is truly a public trust. This explains the choice of language in the clause and provides clues about its meaning. This book thus serves as a reference source for scholars seeking to understand the intellectual foundations of one of the Constitution's most important clauses.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).